Electrospun melamine‐blended activated carbon nanofibers for enhanced control of indoor CO2. Issue 28 (18th March 2019) - Jeong, Dongwon; Jie, Wang; Adelodun, Adedeji A.; Kim, Sangbum; Jo, Youngmin
ABSTRACT: Electrospun carbon nanofibers were activated with melamine–polyacrylonitrile [melamine‐blended carbon nanofibers (MACNFs)] for use as a fibrous adsorbent for indoor CO2 removal. Although, melamine doping was intended solely to incorporate basic nitrogen functionalities on the nanofibers, it also shortened fabrication time, conserving time, and energy cost. The specific surface area and microporosity of the fibers were enhanced from 412 m 2 g −1 and 0.1646 cm 3 g −1 to 547 m 2 g −1 and 0.220 cm 3 g −1, respectively, upon final CO2 activation of the nanofibers. With the chemical properties, we observed significant tethering of pyridine functionality. The sample, MACNF‐7 (10 mL of polymer solution doped with 0.7 g of melamine), provided the optimum melamine doping condition to achieve the highest CO2 adsorption capacity of 3.15 mmol g −1 . The adsorption performance was based on simultaneous improvement in microporosity (physical) and surface basicity (chemical) properties of the adsorbent. However, in a binary mixture with nitrogen, the selective adsorption of CO2 showed the predominance of the improved surface basicity over microporosity. The highest CO2 selective capture (1.22 mmol g −1 ) was occurred for a CO2 :N2 ratio of 0.15:0.85, with a selectivity of 58.19 at 273 K. In a regeneration test, stable and robust performance was achieved more than five cycles. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47747. Abstract :